Transcriptional profiles of the response of methicillin-resistant staphylococcus aureus to pentacyclic triterpenoids - Chung, P.Y.; Chung, L.Y.; Navaratnam, P. (Public Library of Science, 2013)
Staphylococcus aureus is an important human pathogen in both hospital and the community that has demonstrated resistance to all currently available antibiotics over the last two decades. Multidrug-resistant isolates of methicillin-resistant S. aureus (MRSA) exhibiting decreased susceptibilities to glycopeptides has also emerged, representing a crucial challenge for antimicrobial therapy and infection control. The availability of complete whole-genome nucleotide sequence data of various strains of S. aureus presents an opportunity to explore novel compounds and their targets to address the challenges presented by antimicrobial drug resistance in this organism. Study compounds alpha-amyrin 3 beta-hydroxy-urs-12-en-3-ol (AM), betulinic acid 3 beta-hydroxy-20(29)-lupaene-28-oic acid (BA) and betulinaldehyde 3 beta-hydroxy-20(29)-lupen-28-al (BE) belong to pentacyclic triterpenoids and were reported to exhibit antimicrobial activities against bacteria and fungi, including S. aureus. The MIC values of these compounds against a reference strain of methicillin-resistant S. aureus (MRSA) (ATCC 43300) ranged from 64 mu g/ml to 512 mu g/ml. However, the response mechanisms of S. aureus to these compounds are still poorly understood. The transcription profile of reference strain of MRSA treated with sub-inhibitory concentrations of the three compounds was determined using Affymetrix GeneChips. The findings showed that these compounds regulate multiple desirable targets in cell division, two-component system, ABC transporters, fatty acid biosynthesis, peptidoglycan biosynthesis, aminoacyl-tRNA synthetase, ribosome and beta-lactam resistance pathways which could be further explored in the development of therapeutic agents for the treatment of S. aureus infections.